INOVASI MEDIA PEMBELAJARAN DIGITAL UNTUK MENINGKATKAN PARTISIPASI AKTIF SISWA - Faizatil Hasani; Rifka Wulandari; Moh Dzaky Rabbani (Kampus Akademik Publiser, 2025)
Education faces the challenge of adapting to the increasingly complex needs of students in the ever-evolving digital era. One of the aims of this research is to study new types of digital learning media that have the potential to increase active student participation. This research analyzes literature and looks at various interactive learning media, such as learning videos and gamification platforms. The research results show that the use of digital learning media increases student engagement and improves their critical and creative thinking abilities. Therefore, the use of technology in education is very important to make the learning environment more interesting and appropriate to the times.